Strategy Analysis Of BBPOM Pekanbaru Implementing A Communication Management Program Regarding Hazardous Halal-Haram Cosmetics From The Islamic Education Perspective - Rosmala Rosmala; Syukur Kholil; Nursapiah Harahap (Edukasi Islami : Jurnal Pendidikan Islam, 2022)
Communication management is the role of management in communicating effectively. The purpose of this research was to find out how BBPOM Pekanbaru can inform, educate, and communicate (ICE) with the public in Pekanbaru about the phenomenon of dangerous cosmetics. Sources of data are referred to journals, magazines, websites, and newspapers related to the dangerous cosmetics phenomenon. A qualitative research method was implemented, and the POAC (planning, organizing, acting, and controlling) concept on how to communicate was used as a reference. BBPOM Pekanbaru has implemented information sharing, counseling, and the ICE program by conducting 12 times of knowledge sharing through Instagram, Twitter, and Facebook and a 14-time discussion program using video, local television, and radio about dangerous cosmetics in Pekanbaru. Many programs have been implemented as per the yearly program target, but BBPOM needs additional resources to improve the control system. Communication management is very important from an Islamic perspective because everything must be done correctly.